2013
DOI: 10.1016/j.ajog.2013.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Identification of intracellular bacteria in the basal plate of the human placenta in term and preterm gestations

Abstract: Objective Bacteria have been identified in different regions of the placenta. Here, we tested the hypothesis that the maternal basal plate of the placenta harbors microbes which may be associated with adverse pregnancy outcomes. Study Design We performed a cross-sectional study of pregnancies from a single tertiary care hospital. Maternal medical and obstetric characteristics were obtained and pregnancies followed prospectively for outcomes and placental collection. After delivery, systematic random sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
290
1
19

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(319 citation statements)
references
References 41 publications
9
290
1
19
Order By: Relevance
“…Most recently, it has been shown that the placenta harbors a microbiome more similar to that of the non-pregnant human oral microbiome (75). These data support other studies documenting the presence of Gram-negative bacteria in the placental samples in the absence of infection (77), and support the notion that the fetal gut maybe colonized within the intrauterine milieu. However, it is important to note that the presence of bacterial DNA is not the same as live bacteria; and thus far live commensal bacterial populations have not been demonstrated to be present within the placenta.…”
Section: Fetal Gut Microbiome Acquisition In Uterosupporting
confidence: 80%
“…Most recently, it has been shown that the placenta harbors a microbiome more similar to that of the non-pregnant human oral microbiome (75). These data support other studies documenting the presence of Gram-negative bacteria in the placental samples in the absence of infection (77), and support the notion that the fetal gut maybe colonized within the intrauterine milieu. However, it is important to note that the presence of bacterial DNA is not the same as live bacteria; and thus far live commensal bacterial populations have not been demonstrated to be present within the placenta.…”
Section: Fetal Gut Microbiome Acquisition In Uterosupporting
confidence: 80%
“…Essa situação pode ser o reflexo da utilização de antibióticos no tratamento empírico da sintomatologia genitourinária, sem confirmação laboratorial da colonização. Nesses casos, a antibioterapia erradica as bactérias, mas poderá não ser o suficiente para travar o processo inflamatório subjacente 14,15 . Estudos demonstraram que, apesar da presença de bactérias em 80% das RPM-PT, esta por si só não é suficiente para causar PPT, tendo sido identificada em membranas fetais de grávidas a termo em trabalho de parto ou não 14,15 .…”
Section: Discussionunclassified
“…Nesses casos, a antibioterapia erradica as bactérias, mas poderá não ser o suficiente para travar o processo inflamatório subjacente 14,15 . Estudos demonstraram que, apesar da presença de bactérias em 80% das RPM-PT, esta por si só não é suficiente para causar PPT, tendo sido identificada em membranas fetais de grávidas a termo em trabalho de parto ou não 14,15 . No entanto, demonstramos uma elevação significativa dos parâmetros infecciosos (PCR e leucócitos) no grupo PPTe, reforçando, dessa forma, os dados existentes na literatura 5-7 que apontam para um eventual processo inflamatório sistémico, e não localizado, como um dos potenciais fatores para o desencadear de todo o processo do trabalho de parto pré-termo espontâneo.…”
Section: Discussionunclassified
“…[7][8][9][10] Interestingly, one report described the detection of bacteria by light microscopy following Giemsa, Gram, and Brown-Hopps staining of paraffin tissue sections of the basal plate of the placenta in 27% of pregnant women without a significant link to chorioamnionitis or preterm birth. 16 Strikingly, the authors highlighted the intracellular localization of the detected bacteria reminiscent of invasive infection rather than colonization. 16 Similar to the COMMENTARY MucosalImmunology | VOLUME 10 NUMBER 3 | MAY 2017…”
Section: Discussion Of the Available Evidencementioning
confidence: 99%
“…16 Strikingly, the authors highlighted the intracellular localization of the detected bacteria reminiscent of invasive infection rather than colonization. 16 Similar to the COMMENTARY MucosalImmunology | VOLUME 10 NUMBER 3 | MAY 2017…”
Section: Discussion Of the Available Evidencementioning
confidence: 99%